دورة حياة حشرة أبي دقيق الملفوف الكبير Pieris brassicae L (Lepidoptera: Pieridae) على نبات الملفوف تحت الظروف المخبرية - رمضان, علي; أحمد, محمد; بدّور, زينة (Latakia University Journal -Biological Sciences Series, 2020)
Cabbage Large Butterfly Pierisbrassicae L. (Lepidoptera: Pieridae) is the most important pest oncole crops,which cause economic damages for Cabbage in the Syrian Coastal Region. The aim of this study was to study the life cycle of P. brassicae on cabbage under the laboratory conditions. The laboratory study was conducted in the insect laboratory in the Department of Biological Control, Directorate of Agriculture during season 2017-2018. The results showed that this insect has 5 larval instars, and the average of head-capsule width was: 0.39, 0.68, 1.21, 1.73 and 2.67 mm ( first, second, third, fourth, fifth larval instars), respectively. The average length of the larval stages was: 4.35, 11.93,16, 26.87 and 40.79 mm respectively. The mortality was: 2, 6, 8.51, 9.3, 7.69, 2.78 and 2.85 % in the (egg, first, second, third, fourth, fifth larval instars, and pupa), respectively. Eggs were laid in batches with 127.2 eggs/batch. Female have laid 1.93 batches. Female fecundity was 245.49 eggs, and the fertility was 98%. تعد حشرة أبي دقيق الملفوف الكبير Pieris brassicae L(Lepidoptera: Pieridae) آفة رئيسة على محصول الملفوف في الساحل السوري حيث تسبب أضراراً اقتصادية هامة. ونظراً لأهمية هذه الآفة تمت دراسة دورة حياة P.brassicaeعلى نبات الملفوف تحت الظروف المخبرية. نفّذت الدراسة المخبريّة في مخبر الحشرات ضمن دائرة المكافحة الحيوية في مديرية زراعة اللاذقية, خلال موسم النمو 2017-2018. بينت نتائج الدراسة المخبريّة أن لحشرة أبي دقيق الملفوف الكبير خمسة أعمار يرقية وأن متوسط عرض كبسولة الرأس في الأعمار اليرقية الخمسة قد بلغ: 0.39، 80.6، 1.21، 1.73، 2.67ممعلى التوالي، وقد بلغ متوسط طولاليرقات في الأعمار الخمسة 4.35، 11.93، 16، 26.87، و40.79 ممعلى التوالي. في حين بلغ متوسط مدّة التطور لكل من البيضة,اليرقة, والعذراء 3.42، 21.92, 6 يوم,على التوالي. بلغت نسبة الموت للأطوار المختلفة 2، 6، 8.51، 9.3، 7.69، 2.78 و 2.85 % (البيضة, العمر اليرقي الأول, الثاني, الثالث, الرابع, الخامس والعذراء)على التوالي, في حين بلغت مدة التطور الإجمالية 31.34 يوم. بلغ متوسط عدد لطع البيض للأنثى الواحدة 1.93،في حين بلغ متوسط عدد البيض في اللطعة الواحدة للأنثى 127.2 بيضة/اللطعة، وبلغت خصوبة الأنثى (Fecundity) 245.49 بيضة, بينما بلغت نسبة البيض الفاقس(Fertility) 98%.